Pulmonary hypertension or cardiology aerobatics - I. E. Chazova (IP Morozov P.V., 2020)
Pulmonary hypertension (PH) is a group of diseases with a hemodynamic pattern of progressive increase in pulmonary vascular resistance (PVR) and pulmonary artery pressure (PAP), which leads to right ventricular dysfunction and the development of right ventricular heart failure.